Incorporation of pora network connerctivity on the prediction of binary liquid phase adsorption of flavour esters in activated carbon - Suryadi Ismadji (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2005)
The structural heterogeneity of activated carbon is a result of the existence of micropores, mesopores, and macropores of different sizes and shapes, randomly connected in a pore network. In a pore network, some of the pores that are large enough to accommodate the probe molecules may be accessible through smaller pores that only permit the passage of probe molecules having a smaller size. In the adsorption process, especially involving large and complex probe molecules, the pore network connectivity is very important, and governs the transport and reaction properties of the pores. A method for incorporation of the pore network connectivity along with lAST (Ideal Adsorbed Solution Theory Method) on the prediction of binary component adsorption isotherm is proposed in this article. IAST is used in conjunction with the modified DR (Dubinin-Radushkevich) single component isotherm, and is found that the incorporation of the connectivity can improve the accuracy of model inpredicts the multicomponent adsorption performance.Keywords: Adsorption, IAST, Pore Network ConnectivityAbstrak Pore network connectivity memegang peranan yang penting dalam proses adsorpsi yang melibatkan senyawa senyawa kompleks. Pada makalah ini diusulkan suatu metode yang menggabungkan Pore network connectivity dan persamaan IAST untuk prediksi isotherm adsorpsi senyawa biner. Untuk mendapatkan isotherm adsorpsi dilakukan percobaan dengan menggunakan ethyl propionate dan ethyl butyrate sebagai adsorbate dan sebagai adsorbent digunakan karbon aktif Filtrasorb F-400 dan Norit ROW 0.8. Untuk menggambarkan isotherm adsorpsi dari hasil percobaan digunakan persamaan The Ideal Adsorbed Solution Theory dengan modifikasi persamaan isotherm adsorpsi dari Dubinin-Radushkevich dan Pore network connectivity. Dari hasil yang dipero/eh dapat disimpulkan bahwa persamaan yang melibatkan pengaruh pore network connectivity dapat meningkatkan unjuk kerja dari persamaan isotherm multi komponen untuk prediksi data data percobaan adsorpsi biner.Kata Kunci: Adsorpsi, IAST, Pore Network Connectivity